KEMAMPUAN KOGNITIF TOKOH UTAMA CERPEN JANNATU AL-ATHFA - Mochammad Faizun (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
This study aims to determine the cognitive abilities of the main character in the short story Heaven for Children by Najib Mahfudz. Cognitive abilities are one of the developmental aspects of knowledge or understanding, namely all psychological processes related to how a person learns and thinks about the environment. The main character in the short story is a child who talks with his father about divinity and death. In the conversation the researchers found that the child could not understand some of the father's explanations. This is likely influenced by the thinking ability of children who have difficulty understanding conceptual things. This research uses descriptive qualitative method. Results from this research is expected to be able to explain the ability of the main character in the short story so that it becomes learning for parents or teachers in explaining conceptual things to children